2021
DOI: 10.1245/s10434-021-10454-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Intraoperative Ultrasound Localization for Breast-Conserving Surgery in a Large, Integrated Health Care System is Feasible and Effective

Abstract: Background Intraoperative ultrasound (IUS) localization for breast cancer is a noninvasive localization technique. In 2015, an IUS program for breast-conserving surgery (BCS) was initiated in a large, integrated health care system. This study evaluated the clinical results of IUS implementation. Methods The study identified breast cancer patients with BCS from 1 January to 31 October 2015 and from 1 January to 31 October 2019. Clinicopathologic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Various localization methods have obtained negative margins, including palpation-guided, radio-guided, or wire-guided. Our technique aimed to combine an intraoperative ultrasound to guide surgeon-performed wire localization and removal of the breast lesion throughout one procedure under general anesthesia [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various localization methods have obtained negative margins, including palpation-guided, radio-guided, or wire-guided. Our technique aimed to combine an intraoperative ultrasound to guide surgeon-performed wire localization and removal of the breast lesion throughout one procedure under general anesthesia [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews and meta-analyses of reports from centres around the world have demonstrated that IOUS excision of breast cancers is associated with improved margins of excision, lower reoperation rates and smaller volumes of tissue being excised resulting in better cosmetic outcomes. [7][8][9] The technique is also favoured by patients who are able to avoid a painful preoperative procedure such as insertion of a hookwire, and as a result, patients experience less preoperative anxiety and can spend less time in the hospital environment. 2 Other advantages of the IOUS technique include the ability to assess margins of excision on table immediately following the resection, so that if required, additional tissue can be taken at the time thus avoiding the need to return to theatre for reexcision and reduced operating theatre time as on-table specimen sonography obviates the need to send the specimen to the radiology department for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the practice of IOUS localisation to excise impalpable breast lesions is being increasingly utilised and recognised as an appropriate, safe and economically efficient technique . Several reviews and meta‐analyses of reports from centres around the world have demonstrated that IOUS excision of breast cancers is associated with improved margins of excision, lower reoperation rates and smaller volumes of tissue being excised resulting in better cosmetic outcomes 7–9 …”
Section: Discussionmentioning
confidence: 99%
“…The implementation of radioactive seeds needs to be one day before surgery. It is also an invasive procedure that has a high financial cost [ 9 ]. Likewise, wire localization needs to be done in a separate setting before surgery, and it is associated with increased patient anxiety [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…IOUS of the excised surgical specimen could be used to ensure appropriate margins surrounding the whole specimen. If a deficient margin is detected the surgeon is informed and a re-excision of the infiltrated region is performed within the same primary setting [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%